Analisis Isi Pesan Dakwah Pada Akun Instagram Husain Basyaiban @Basyasman - Salsabila Thifal; Dewi Anggrayni; Salati Asmahasanah (KOLONI, 2023)
Social media, especially Instagram, has a significant impact on many things, including as a way of preaching. There are many various Instagram creator accounts, including an Instagram account with the username @basyasman owned by Husein Basyaiban with 1.2 million followers and 374 posts which is used as a medium for preaching and inspires many young people to learn religion and become better. The aim of this research is to determine the content of the religious preaching message displayed on Husein Basyaiban's Instagram account which is analyzed based on the pillars of faith. The research method used is a qualitative approach which aims to explain or describe phenomena by collecting as much data as possible. The research results show that the da'wah messages contained in @basyasyman's Instagram from January 13 2022 – October 21 2022 discuss aqidah da'wah messages. There are 5 posts in the aqidah da'wah message which discuss commands and suggestions to always obey Allah and foster love for Allah and Allah's Messenger by obeying the pillars of faith.